Myotonic dystrophy type 1 (DM1) and speech problems - Cardoso, Inês Lopes (2017)
Myotonic Dystrophy type 1(DM1), also called Steinert syndrome, is a multisystemic disorder transmitted in an autosomal dominant manner, characterized by myotonia. Muscles involved in voluntary movement are highly affected by myotonia especially distal muscles of upper limbs. Patients with DM1 present a myopathic face and oropharynx weakness. Reduced motor mobility and saliva flux can lead to gingival inflammation and periodontal disease together with other oral manifestations like disturbances at the temporomandibular articulation. Main causes of death are pneumonia and cardiac arrhythmias. Although the etiology of this syndrome is well known, a specific treatment for this disease is still not available. Nowadays, treatments consist on the relief of existing symptoms, in an attempt to give a better life quality to patients. It is very important to implement actions that can prevent complications and this is why treatments should be applied in an early stage of the disease. It is the aim of this paper to clarify the etiology, systemic characteristics of the syndrome and in particular discuss how myotonia can lead to speech disturbances and present strategies to deal with this particular problem.